2020
DOI: 10.1158/1078-0432.ccr-20-1899
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Pleomorphic Dermal Sarcomas Reveals Fibroblastic Differentiation and Susceptibility to Immunotherapy

Abstract: Purpose: Pleomorphic dermal sarcoma (PDS) is a rare malignant cutaneous tumor with an unknown cell of origin. Locally defined tumors can be treated by curative excisions, whereas advanced stages of the disease are difficult to treat, using standard regimens.Experimental Design: We performed whole-exome sequencing on a cohort of 28 individuals and corresponding transcriptomic analysis on 21 patients, as well as quantitative IHC image analysis on 27 patients.Results: PDS exhibits a universally high mutational lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 37 publications
5
44
0
22
Order By: Relevance
“…Our results showed that AFX exhibits high TMB, also known as a mutational load. The PDS subgroup also evidenced high TMB, which is in line with a previous report [ 11 ]. TMB is affected by different sources, including exposure to mutagenic agents such as ultraviolet light in melanoma and cigarette smoke in lung cancer [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that AFX exhibits high TMB, also known as a mutational load. The PDS subgroup also evidenced high TMB, which is in line with a previous report [ 11 ]. TMB is affected by different sources, including exposure to mutagenic agents such as ultraviolet light in melanoma and cigarette smoke in lung cancer [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a study evidenced DNHD1 , RTN1 , RTL1 , ZBTB7A , NCKAP5L , and FAM200A as significantly mutated genes in PDS and demonstrated recurrent point mutation in DDX31 (R72K) in five out of 28 PDS by performing whole-exome sequencing. Additionally, a high tumor mutational burden (TMB) with an average of 42.7 nonsynonymous variants per mega base was reported in the analyzed PDS cohort [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low TMB has been observed in subtype-specific cohorts of alveolar soft-part [75], Ewing [76,77], synovial [78], and osteosarcoma [76]. Tumor mutational burden was not associated with immune biomarkers in pleomorphic dermal sarcoma [78,79] or survival in synovial sarcoma [78], but negatively correlated with survival in pediatric Ewing sarcoma [80]. Currently there are no prognostic data on microsatellite instability.…”
Section: Tumor Mutation Burden and Microsatellite Instabilitymentioning
confidence: 99%
“…Of note, studies do report select cases with high TMB in angiosarcoma [81,82], malignant peripheral nerve sheath tumor [82], and pleomorphic dermal sarcoma [79]. Angiosarcoma tumors with high TMB are superficially located and show UV-dominant mutations [81,82] as are seen in melanomas, a tumor type responding to checkpoint inhibitors.…”
Section: Tumor Mutation Burden and Microsatellite Instabilitymentioning
confidence: 99%
“…One of the most widely used area is pharmacogenomics, which analyzes how an individual's genome will affect the therapeutic response [30]. For example, these alterations may entail identifying individual targetable variants or estimating tumor mutational load to predict response to treatment, such as immune-checkpoint inhibitors [31,32]. Another emerging field in genetics is the use of non-invasive circulating tumor DNA to monitor the treatment responses of the patients as well as to characterize the resistance mechanisms [33,34].…”
Section: Dna-sequencingmentioning
confidence: 99%